Dysplastic crypt-rings in tandem: A novel histologic parameter in tubular adenomas - Rubio, Carlos A.; Vieth, Michael; Lang-Schwarz, Corinna (Annals of Diagnostic Pathology, 2024)
Descriptions of the various dysplastic crypt phenotypes occurring in TA have remained unattended in the literature. Recently, new crypt-phenotypes, characterized by crypt rings in tandem (CRT), and by dysplastic crypt rings in tandem (DCRT) were described in IBD, and in in IBD-associated dysplasia, respectively. Here, we report the occurrence of DCRT in 40.4 % (n = 59) out of 146 consecutive tubular adenomas of the colorectum (TA). The number of DCRT varied: 10 TA had two DCRT, seven TA had three DCRT, two TA, four DCRT and the remaining two TA had ≥ five DCRT. The frequency of DCRT was influenced by TA-size; larger TA (≥ 5 mm) had significantly more DCRT than smaller TA (<5 mm). Conversely, the frequency of TA with DCRT was not influenced by age, gender, or localization. Since only 1 or 2 sections were available per TA, the number of DCRT in the entire TA should be higher than those shown in Results. Historical controls in human and rodent normal colorectum showed no CRT. Moreover, DCRT were not found in 781 historical non-polypoid colorectal adenomas. The present finding might encourage searching for DCRT, the final goal being to achieve a more elaborated microscopic narrative of TA, the most prevalent of all colorectal adenomas.
CRIS-Team Scopus Importer:2024-05-10
Keywords: Colon; Dysplastic crypt rings; Tubular adenomas